Developing Audio-Visual Learning Media Based on Local Wisdom to Improve Students’ Storytelling Abilities In Indonesian Language Lessons in Grade V of Muhammadiyah 1 Elementary School, Sorong City - Sarti, Marini (LENTERNAL: Learning and Teaching Journal, 2025)
This study aims to develop audio-visual learning media based on local wisdom that can improve the storytelling ability of fifth grade students of Muhammadiyah 1 Elementary School, Sorong City. In addition, this study also aims to test the validity, practicality, and effectiveness of the media in supporting the Indonesian language learning process. The method used is a mixture of quantitative and qualitative approaches. Quantitative data were obtained through expert validation results, pretest and posttest scores, and assessment of student learning outcomes. Meanwhile, qualitative data were collected through observation, interviews, and responses from students as well as input from language, material, and media experts. Media development was carried out using the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The media developed contains West Papuan folklore, which aims not only to improve storytelling skills, but also to instill local cultural values in students. The trial results showed no significant revisions, so the media was tested directly in the field. The results showed an increase in students’ storytelling ability from 58.64% to 80.14%, or an increase of 21.5%. This increase indicates that the media is in the very high category on the student understanding scale. The use of audio-visual media based on local wisdom has been proven to increase learning motivation, strengthen pride in one’s own culture, and foster students’ self-confidence in telling stories in public. This media is also a solution to reduce boredom in the conventional learning process